Quality evaluation of entrepreneurship education in higher education based on CIPP model and AHP-FCE methods - Fan, Xinqiao; Tian, Siyu; Lu, Zhenglan; Cao, Yirong (Frontiers in Psychology, 2022)
Entrepreneurship education has become an important component of higher education development. This paper uses the techniques of the analytic hierarchy process (AHP) and the fuzzy comprehension evaluation (FCE) method to develop a quality evaluation system featuring four factors: entrepreneurship education courses, teachers, entrepreneurial environment and students participation. Relevant factors and indicators are quantified by the AHP, and then a scientific evaluation system is established. Finally, the paper applies the applied FCE model to draw the conclusions on comprehensive evaluation regarding the quality of entrepreneurship education.